Die Erfurter Historienbibel: (Historienbibel Gruppe VI) - Bentzinger, Rudolf (Deutsche Texte des Mittelalters, 2016)
"The volume provides the text of the Erfurt Popular Bible (an expanded bible translation with commentary) in a parallel presentation of two Erfurt manuscripts from the 1420s. The text reprint indicates the connections to the vulgate and other sources, and the introduction covers relevant biblical historical, codicological, and language historical issues, thereby presenting an important textual example of late Medieval bible history." -- Publisher's website